Influences of (in)congruences in psychological entitlement and felt obligation on ethical behavior - Chen, Qin; Shen, Yifei; Zhang, Li; Zhang, Zhenduo; Zheng, Junwei; Xiu, Jing (Frontiers in Psychology, 2023)
Introduction Psychological entitlement and felt obligation are two correlated but distinctive conceptions. Prior studies have mainly explored their influences on employees' (un)ethical behavior, respectively. Recently, several studies suggest the interactive impacts of psychological entitlement with felt obligation on individual behavioral choices. In consistency with these studies, the present study focuses on the influences of (in)congruences in psychological entitlement and felt obligation on employees' (un)ethical behavior. Methods A two-wave multi-source questionnaire survey is conducted to collect 202 matched questionnaires from full-time Chinese workers. The polynomial regression with response surface analysis is employed to test hypotheses. Results The results indicate that: (1) employees have higher levels of work engagement and helping behavior but lower levels of unethical behavior when their psychological entitlement and felt obligation are balanced at higher levels rather than lower levels; (2) employees have higher levels of work engagement and helping behavior but lower levels of unethical behavior when they have higher levels of felt obligation but lower levels of psychological entitlement compared to those having lower levels of felt obligation but higher levels of psychological entitlement; and (3) work engagement mediates the relationship between (in)congruences in psychological entitlement and felt obligation and employees' helping behavior and unethical behavior. Discussion This study provides a novel insight into the interactive influences of (in)congruence in psychological entitlement and felt obligation on employees' ethical behavioral choices.